THE EFFECT OF INFORMATION ASYMMETRY AND ACCOUNTING CONSERVATISM ON FINANCIAL PERFORMANCE - Raudhatinur; Ihsan Arif; Ismed Wijaya; Putri Yamin; Yusnidar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Financial performance is a key indicator used to evaluate a company’s success in creating value for shareholders. From the perspective of agency theory, conflicts of interest between managers (agents) and owners (principals) may lead to information asymmetry, which can affect decision-making quality and corporate performance. On the other hand, accounting conservatism is considered a governance mechanism that helps reduce agency conflicts and enhance the credibility of financial reporting. In healthcare sector companies listed on the Indonesia Stock Exchange during the 2022–2023 period, post-pandemic industry dynamics and global economic pressures demand greater transparency and prudence in financial reporting. Therefore, it is important to examine whether information asymmetry and accounting conservatism influence corporate financial performance. This study employs a quantitative approach using secondary data in the form of annual financial statements of healthcare sector companies listed on the Indonesia Stock Exchange for the 2022–2023 period. The sampling technique used is purposive sampling based on predetermined criteria, resulting in 29 companies as the research sample. Data analysis was conducted using multiple linear regression, including classical assumption tests (normality, heteroscedasticity, and multicollinearity), partial tests (t-test), simultaneous test (F-test), and the coefficient of determination (Adjusted R²). The findings indicate that partially, Information Asymmetry does not have a significant effect on Financial Performance (t-value = 0.999; sig. = 0.322 > 0.05). Conversely, Accounting Conservatism has a positive and significant effect on Financial Performance (t-value = 2.991; sig. = 0.004 < 0.05). Simultaneously, Information Asymmetry and Accounting Conservatism significantly influence Financial Performance (F-value = 4.644; sig. = 0.014 < 0.05). The Adjusted R² value of 0.519 indicates that the independent variables explain 51.9% of the variation in Financial Performance, while the remaining 48.1% is influenced by other variables not included in the model. This study concludes that Accounting Conservatism plays an important role in improving Financial Performance in healthcare sector companies. Meanwhile, Information Asymmetry is not proven to have a significant effect on Financial Performance. Simultaneously, both variables significantly contribute to Financial Performance, although other factors outside the model also influence corporate performance. These findings emphasize the importance of prudence in financial reporting as a mechanism to reduce agency conflicts and enhance firm value.